Examination of Bamboo Measurement Method for Biomass Estimation in the Paung Laung Reserve Forest, Myanmar - Kitahara, Fumiaki; Sato, Tamotsu; Win, Billy Ne; Takao, Gen; Win, Tun Tun; Maung, Kyaw Win (AGRIVITA, Journal of Agricultural Science, 2019)
The objective of this study was to investigate a method of measuring bamboo diameter at breast height (DBH) for biomass estimation using Monte Carlo sampling. The data for this study were collected in Paung Laung Reserve Forest, Myanmar. The research developed two different methods for determining required sampling numbers based on changes in the coefficient of variation (CV) with the sampling ratio and sampling size using 37 plots of bamboo. These sampling numbers were derived from the sampling ratio with a CV less than 10 % and the stability of the CV. The error ratios of the two results between measured and estimated bamboo biomass were 6.0 % and 6.9 %. It will be necessary to assess the balance between the estimation accuracy and survey time for carbon stock estimation of bamboo, which is indispensable for an accurate forest carbon accounting in Myanmar.